Impedance analysis and equivalent circuit modelling of cells subjected to sinusoidal vibration test using electrochemical impedance spectroscopy - Bangal, Ojas A.; Chaturvedi, Vikash; Babu, P. K. Ajeet; Shelke, Manjusha V. (2019 IEEE Transportation Electrification Conference (ITEC-India), 2019)
Electrochemical impedance spectroscopy is a multipurpose and non-destructive characterization technique in the analysis of electrochemical power sources such as Li-ion cells. The nyquist curve obtained by EIS spectrum of the cell gives information about its overall health. Curve fitting of the EIS nyquist plots further helps in determining the Equivalent Circuit Model (ECM) for a particular cell. In this paper commercial Li-ion cells from three different chemistries; Lithium Nickel Manganese Cobalt Oxide (NMC), Lithium Cobalt Oxide (LCO) and Lithium Iron Phosphate (LFP) are subjected to sinusoidal vibration test as per testing standard mentioned in United States Advanced Battery Consortium (USABC). The EIS measurement of the test cells have been carried out before and after the vibration tests. Curve fitting is carried out on the EIS plots and ECM for the cells is obtained. The components present in ECM and their actual values are estimated from the curve fitting analysis. The magnitude of various resistances like equivalent series resistance (R s ), charge transfer resistance (R ct ) and solid electrolyte interphase resistance (R sei ) is evaluated. This technique is also used in determining the capacitances inside the cell, mainly capacitance (C sei ) due to Solid Electrolyte Interphase layer (SEI) and capacitance due to double layer (C dl ) formation at electrode surface. The resistance in the cell is found to be increased and the capacitances values are decreased after vibration test. Bode plot for the cells are analysed and the overall change in the impedance of cell due to the vibration test is investigated as well. Scanning electron microscopy technique is used on cell electrodes, after vibration test, to validate the actual damage that took place within the cell. The study reveals that the EIS can be used as a non-destructive tool to check cell health after mechanical abuse.